Phylogenetic position and redescription of Orchestina manicata Simon, 1893 (Araneae: Oonopidae) - Sasanka Ranasinghe; Suresh P. Benjamin (Journal of Insect Biodiversity and Systematics)
The goblin spider Orchestina manicata Simon, 1893 (Araneae: Oonopidae) has remained taxonomically unrevised and has not been phylogenetically placed until now. In this study, O. manicata is redescribed based on newly collected specimens from Sri Lanka. The habitus and genital morphology of both males and females are illustrated and described, with photographs provided for the first time. Orchestina manicata is recognised by the embolus which has a triangular bifid tip and a swollen palpal tibia. The abdomen in males and females is rounded. Through a phylogenetic analysis of 51 morphological characters, combined with molecular data from two target genes (28S, 18S), we present the first hypothesis regarding the phylogenetic placement of this species within the genus.